2009
DOI: 10.1111/j.1476-4431.2009.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of mycophenolate mofetil as a rescue agent in the treatment of severe generalized myasthenia gravis in three dogs

Abstract: This is the first report of the use of IV MMF as adjunctive treatment in dogs with severe generalized myasthenia gravis. Outcome was favorable in all 3 dogs and no adverse effects were noted from the MMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 34 publications
(34 reference statements)
2
47
0
1
Order By: Relevance
“…The most common adverse reactions associated with MMF administration in dogs with naturally occurring immune‐mediated diseases are weight loss, GI upset and mild allergic reactions during parenteral administration (Dewey et al , Lange et al ). In this case series, GI side effects due to MMF therapy were common, which is consistent with previous studies (Dewey et al , Banyard & Hassett , Broaddus et al , Yuki et al , Abelson et al , Dewey et al , Ginel et al , Wang et al , West & Hart ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most common adverse reactions associated with MMF administration in dogs with naturally occurring immune‐mediated diseases are weight loss, GI upset and mild allergic reactions during parenteral administration (Dewey et al , Lange et al ). In this case series, GI side effects due to MMF therapy were common, which is consistent with previous studies (Dewey et al , Banyard & Hassett , Broaddus et al , Yuki et al , Abelson et al , Dewey et al , Ginel et al , Wang et al , West & Hart ).…”
Section: Discussionsupporting
confidence: 92%
“…Another study has found that maximal inhibition of IMPDH occurs approximately 2 to 4 hours after MMF administration, suggesting a rapid onset of action (Langman et al ). A case series of three dogs with myasthenia gravis managed with MMF reported signs of clinical remission occurring within 48 hours of initiation of MMF, further suggesting MMF may be a rapidly acting immunosuppressant (Abelson et al ). In the present case series, the platelet count recovery was relatively rapid.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic options in dogs and cats with TAMG are similar to human TAMG comprising pyridostigmine, corticosteroids, azathioprine, mycofenolate mofetil [129,135] and thymoma surgery. The latter is not only indicated for oncologic reasons [136] but can reduce autoantibody titers and myasthenic symptoms [128].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[29][30][31] The acquired disease is usually a temporary state and may resolve over many months of supportive care. In addition, the immunosuppressive effects of corticosteroid therapy may lead to rapid respiratory deterioration in patients with aspiration pneumonia.…”
Section: Aortic Thromboembolismmentioning
confidence: 99%